2007
DOI: 10.17221/2228-pse
|View full text |Cite
|
Sign up to set email alerts
|

Modification of cadmium toxicity in pea seedlings by kinetin

Abstract: The effect of foliar application of kinetin on the growth and some physiological processes of pea plants growing in soil supplemented with 25 or 50µM Cd were studied. Cadmium treatment inhibited the growth rate, chlorophyll (Chl) content, net photosynthesis (P N ), content of soluble sugars and free amino acids of either shoots or roots. The application of kinetin (kin) enhanced the growth rate, Chl content, P N , soluble sugars and free amino acids content of shoots and roots; dark respiration rate (R D ), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…Recently, some studies have revealed that CKs are involved in plant responses to heavy metal stresses (Al-Hakimi 2007;Lukatkin et al, 2007;Gemrotová et al, 2013;Pavlíková et al, 2014a,b;Singh and Prasad, 2014). Treatment of maize seeds with kinetin (a synthetic CK) resulted in relief of negative symptoms of Zn and nickel (Lukatkin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have revealed that CKs are involved in plant responses to heavy metal stresses (Al-Hakimi 2007;Lukatkin et al, 2007;Gemrotová et al, 2013;Pavlíková et al, 2014a,b;Singh and Prasad, 2014). Treatment of maize seeds with kinetin (a synthetic CK) resulted in relief of negative symptoms of Zn and nickel (Lukatkin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Plant hormones have been reported as active members of signal transduction cascade involved in the plant stress responses [16]. Studies have shown that exogenous KN supplementation can promote growth and alleviate metal toxicity [17][18][19][20][21][22]. However, other works showed that KN if present in excess induces increased ethylene production, generation of ROS and alteration in antioxidant system which cause adverse effects on plant metabolism and may even lead to cell death [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous cytokinins application enhanced manganese (Mn) tolerance and the antioxidant defense system (Gangwar et al, 2010), reduced Cd-induced alterations (Al-Hakimi, 2007). Exogenous application of cytokinin-like PGR kinetin decreased toxic effects of cadmium (Cd) (Munzuroglu, Zengin, 2006), and thidiazuron had protective effect on cucumber seedlings exposed to heavy metals (Lukatkin et al, 2003).…”
Section: +mentioning
confidence: 99%
“…The efficacy of kinetin and other cytokinin-like substances was evaluated according to the following parameters: in pea seedlings by the rate of growth, soluble sugars and chlorophyll content, and on the rate of photosynthesis (Al-Hakimi, 2007); in zucchini -on the rate of cell division and growth (Stoynova-Bakalova, Petrov, 2010); in Mexican Palo Verde -by alterations in catalase and ascorbate peroxidase activities (Zhao et al, 2011); in maize cucumber -by seed germination and growth of axial organs (Lukatkin et al, 2007); in cucumber -by superoxide generation, LPO intensity, carotenoid content in leaves (Bashmakov et al, 2012).…”
Section: Introductionmentioning
confidence: 99%